1995
DOI: 10.5694/j.1326-5377.1995.tb138403.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression of plasma glutamine concentration after exercise stress and its possible influence on the immune system

Abstract: ObjectiveTo determine whether plasma glutamine levels can be used as an indicator of exercise‐induced stress, and to consider the possible effects of low plasma glutamine concentrations on the immune system. MethodsWe used two exercise regimens: in Trial 1 seven male subjects were randomly stressed on a treadmill at 0, 30%, 60%, 90% and 120% of their maximal oxygen uptake $(Vo2max); in Trial 2 five highly trained male subjects underwent intensive interval training sessions twice daily for ten days, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 23 publications
2
45
2
4
Order By: Relevance
“…These authors used a bioassay method for the assessment of glutamine (using the glutamine-dependent growth of Escherichia coli bacteria in culture), but the validity of this method can be questioned: factors other than glutamine change in blood plasma during exercise which may aect bacterial growth, thus confounding this particular method of glutamine assay. This method produces resting plasma Table 1 Heart rate (beats á min A1 ) and rating of perceived exertion (RPE) on a scale of 1 to 10 (Borg 1982) glutamine concentrations in excess of 1200 lM (Keast et al 1995;Rowbottom et al 1996) which is about double the concentrations reported using enzymatic spectrophotometric procedures (Rennie et al 1981;Lund 1985;Sewell et al 1994;Castell et al 1995). Thus, there must be some concern that their ®ndings may be an artefact of the bioassay method used to measure glutamine.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…These authors used a bioassay method for the assessment of glutamine (using the glutamine-dependent growth of Escherichia coli bacteria in culture), but the validity of this method can be questioned: factors other than glutamine change in blood plasma during exercise which may aect bacterial growth, thus confounding this particular method of glutamine assay. This method produces resting plasma Table 1 Heart rate (beats á min A1 ) and rating of perceived exertion (RPE) on a scale of 1 to 10 (Borg 1982) glutamine concentrations in excess of 1200 lM (Keast et al 1995;Rowbottom et al 1996) which is about double the concentrations reported using enzymatic spectrophotometric procedures (Rennie et al 1981;Lund 1985;Sewell et al 1994;Castell et al 1995). Thus, there must be some concern that their ®ndings may be an artefact of the bioassay method used to measure glutamine.…”
Section: Discussionmentioning
confidence: 97%
“…Twenty bouts of high-intensity treadmill running for 1 min separated by 2 min of recovery led to a drastic reduction in plasma glutamine concentration at 5 min post-exercise. From a mean, fasting plasma glutamine concentration of 1244 lM at rest, mean concentrations of 702 lM and 560 lM were recorded after the exercise protocol at 90% and 120% O 2max , respectively (Keast et al 1995). These authors used a bioassay method for the assessment of glutamine (using the glutamine-dependent growth of Escherichia coli bacteria in culture), but the validity of this method can be questioned: factors other than glutamine change in blood plasma during exercise which may aect bacterial growth, thus confounding this particular method of glutamine assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood samples were placed on ice for transfer to the laboratory where the plasma was separated by centrifugation (5 min at 1200 x g). The plasma was deproteinized and analysed for L-glutamine according to the method described by Keast et al (1995).…”
Section: Animalsmentioning
confidence: 99%